Ethical principles and editorial standards. - Rodriguez, Daniele; Meloni, Lorenzo; Zanin, Maria; Lavagnolo, Cinzia (Medicina e Morale, 1993)
The study is part of research carried out to evaluate how ethical standards in biomedical experimentation are considered by researchers. Seven hundred and fifty-six intemational medical-scientific journals were examined with the aim of verifying whether the editorial boards subordinated the publication of the articles to the respect for ethical principles in experimentation. The study also examined the ethical question connected to experimentation on animals. The fact that basically little attention is given to the ethical aspects of experimentation both on man and on animals emerges from the study and the Authors consider that this problem can be overcome with a worldwide ethical training project for researchers.